2020
DOI: 10.1186/s12891-020-03448-2
|View full text |Cite
|
Sign up to set email alerts
|

The risk of fracture and prevalence of osteoporosis is elevated in patients with idiopathic inflammatory myopathies: cross-sectional study from a single Hungarian center

Abstract: Background: The prevalence of osteoporosis and risk of fractures is elevated in rheumatoid arthritis (RA), but we have limited information about the bone mineral density (BMD) and fracture risk in patients with inflammatory myopathies. We intended to ascertain and compare fracture risk, bone mineral density and the prevalence of vertebral fractures in patients with inflammatory myositis and rheumatoid arthritis and to assess the effect of prevalent fractures on the quality of life and functional capacity. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 17 A cross-sectional study in Hungary by Vincze et al comparing the prevalence of osteoporosis in IIM and RA patients also found that IIM patients had elevated risks for osteoporosis. 18 It was shown that 60% and 13.5% of participating IIM patients had osteopenia and osteoporosis, respectively, in contrast to 39.5% and 7% in the RA controls.…”
Section: Discussionmentioning
confidence: 96%
“… 17 A cross-sectional study in Hungary by Vincze et al comparing the prevalence of osteoporosis in IIM and RA patients also found that IIM patients had elevated risks for osteoporosis. 18 It was shown that 60% and 13.5% of participating IIM patients had osteopenia and osteoporosis, respectively, in contrast to 39.5% and 7% in the RA controls.…”
Section: Discussionmentioning
confidence: 96%